Pengaruh dosis kalium terhadap intensitas penyakit bercak daun yang disebabkan oleh Cercospora personata pada tanaman kacang tanah - Neuw, Korinus; Daeng, Baso; Martanto, Eko Agus; Andriani, Liz Yanti (Fakultas Pertanian Universitas Papua, 2023)
Cercospora personata is a pathogen that causes leaf spot disease, as one of the important diseases of peanut plants, known to reduce the rate of photosynthesis to reduce plant production by up to 50%. The handling of Cercospora attacks so far is still focused on the method of spraying fungicides. Potassium fertilization is known to increase plant resistance from one of the Cercospora attacks. The right dosage to overcome Cercospora attacks needs to be studied so that the method of fertilizing potassium in peanut plants can be implemented effectively. This study was conducted in an experimental garden using 5 dosages of potassium and repeated 3 times. The composition of the treatment used is: D0 (control), D1 (2 gr of potash fertilizer per plant), D2 (4 gr of potash fertilizer per plant), D3 (6 gr of potash fertilizer per plant) and D4 (8 gr of potash fertilizer per plant). Weekly observations were made on the variables of plant height, number of leaves, number of saplings, as well as the intensity of disease attacks. The results showed that the dose of potassium had a significant effect on several components of plant growth and the intensity of disease attacks. The application of potassium as a fertilizer has a significant influence on the observation components of the number of leaves (plant age 8, 10, and 12 MST), the number of saplings at plant age 10 MST, and the intensity of leaf spot disease attacks (plant age 8, 10, and 12 MST). Plants that were not given potassium showed leaf spot disease attacks with the highest intensity compared to the other four treatments. This pattern was seen at observation ages of 8, 10, and 12 MST.